2009
DOI: 10.1155/2009/954382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Indoor Environment on the Fraction of Exhaled Nitric Oxide in School‐Aged Children

Abstract: BACKGROUND: The fractional concentration of exhaled nitric oxide (FeNO) appears to be a good marker for airway inflammation in children with asthma.OBJECTIVE: To evaluate the effect of environmental exposures on exhaled nitric oxide in a community sample of children.METHODS: The relationship among exhaled nitric oxide, underlying disease and home environmental exposures was examined using questionnaire data and measurement of exhaled nitric oxide in a cross-sectional study of 1135 children that included health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 37 publications
1
25
4
Order By: Relevance
“…30 The authors speculated that forced air heating is associated with lower indoor dust mite levels, whereas electric heating increases indoor dust mite levels and is related to higher formaldehyde concentration, thus increasing the allergic sensitization and levels of FeNO. 31,32 In addition, there are 2 conflicting studies reporting the association between polyvinyl chloride material and FeNO levels.…”
Section: ) Indoor Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The authors speculated that forced air heating is associated with lower indoor dust mite levels, whereas electric heating increases indoor dust mite levels and is related to higher formaldehyde concentration, thus increasing the allergic sensitization and levels of FeNO. 31,32 In addition, there are 2 conflicting studies reporting the association between polyvinyl chloride material and FeNO levels.…”
Section: ) Indoor Air Pollutionmentioning
confidence: 99%
“…The reported associations between smoking exposure and FeNO levels in asthmatic children have been discordant, probably due to methodological biases, such as small sample sizes, heterogeneous study populations, and lack of control for potential confounding factors. 30,35,36 Some studies have not found a significant effect of passive smoking on FeNO in children, 30,36 whereas others suggested that environmental tobacco smoke lowers FeNO levels (Table). 27,35 According to the type of smoke exposure, acute exposure may induce a marked, but transient reduction in FeNO levels related to a negative feedback of iNOS activity, since tobacco smoke contains high concentrations of NO.…”
Section: ) Indoor Air Pollutionmentioning
confidence: 99%
“…Greater exposure to cockroaches, rats, birds or dogs seems to be related with higher asthma prevalence and symptoms. 60,[67][68][69] However, exposure to cats does not seem to increase asthma symptoms, and a recent meta-analysis has even observed a protector effect for asthma from exposure to this animal. 70,71 Others For other diseases, the evidence is less consistent.…”
Section: Lung Cancermentioning
confidence: 99%
“…Spanier et al found that cat and dog sensitizations were associated with increased FeNO [29]. Differently, Kovesi and Dales [32] found that dog ownership, but not cat ownership, was associated with changes in FeNO levels. …”
Section: Indoor Pollutants and Fenomentioning
confidence: 99%